Mexico's PROGRESA : Innovative Targeting, Gender Focus and Impact on Social Welfare - Wodon, Quentin; de la Briere, Benedicte; Siaens, Corinne; Yitzhaki, Shlomo (World Bank, Washington, DC, 2012)
PROGRESA (Programa de Educacion, Salud y Alimentacion) is an innovative Mexican program that provides cash transfers to poor rural households, on condition that their children attend school and their family visits local health centers regularly. Confronted with rising poverty after the economic crisis of 1995, the Mexican government progressively changed its poverty reduction strategy, ending universal tortilla subsidies and instead funding new investment in human capital through PROGRESA. The program gives cash grants to poor rural households, provided their children attend school for 85 percent of school days and the household, visit public health clinics and participate in educational workshops on health and nutrition. Founded in 1997, PROGRESA grew to cover around 2.6 million families by the end of 1999, the equivalent of 40 percent of all rural families, and one in nine families nationally. Operating in 31 of the 32 states, in 50,000 localities and 2,000 municipalities, its 1999 budget of US$777 million equaled 0.2 percent of Mexico's gross domestic product. The high level of funding for PROGRESA, and reduced funding for other programs, was based on a deliberate policy decision - to favor programs that are better targeted to the poor, which involve co-responsibility by beneficiaries, and which promote long-term behavioral change.